Schools and families as institutions of learning in Central Javanese gamelan. Issue 1 (2nd January 2018) - Hand, Rachel
ABSTRACT: The 1950s marked the advent of formal education in traditional Javanese performing arts as educational institutions were established in Central Java. These schools have since become the main route into a performing arts career for most gamelan musicians. This standardised education contrasts with the ways previous generations learnt to play gamelan, which was a process of knowledge acquisition that often arose from a family background in arts and from performing together from a young age. The institutionalisation alleged to have taken place at the arts schools is a source of debate among musicians and others in the industry. However, drawing upon Bourdieu's theory of family, this article argues that the performing artist families which predate schools as sites of learning are themselves examples of institutions. Moreover, as today's arts institutions are largely populated by members of artist families, it appears that one type of institution has, to some extent, become another.